Исследование особенностей мотивации учебной деятельности в младшем школьном возрасте - Пряхин, Е.А. (My University, 2013)
The article discusses the psychological aspect of the problem of motivation of education activity of young age School children. Reveals the essence of the concept of motives and the content of various kinds of motives of educational activities. The article Shows the date of the empirical Studies of the dominant motives of educational activities Students primary School age.